Genome Sequence, Assembly and Characterization of Two Metschnikowia fructicola Strains Used as Biocontrol Agents of Postharvest Diseases - Piombo, Edoardo; Sela, Noa; Wisniewski, Michael; Hoffmann, Maria; Gullino, Maria L.; Allard, Marc W.; Levin, Elena; Spadaro, Davide; Droby, Samir (Frontiers in Microbiology, 2018)
Abstract The yeast Metschnikowia fructicola was reported as an efficient biological control agent of postharvest diseases of fruits and vegetables, and it is the bases of the commercial formulated product "Shemer".. Several mechanisms of action by which M. fructicola inhibits postharvest pathogens were suggested including iron-binding compounds, induction of defense signaling genes, production of fungal cell wall degrading enzymes and relatively high amounts of superoxide anionss. We assembled the whole genome sequence of two strains of M. fructicola using PacBio and Illumina shotgun sequencing technologies. Using the PacBio, a high-quality draft genome consisting of 93 contigs, with an estimated genome size of approximately 26 Mb, was obtained. Comparative analysis of M. fructicola proteins with the other three available closely-relatedclosely related genomes revealed a shared core of homologous proteins coded by 5,776 genes. Comparing the genomes of the two M. fructicola strains using a SNP calling approach resulted in the identification of 564,302 homologous SNPs with a total of 2,0042,004 predicted high impact mutations. The size of the genome is exceptionally high when compared with those of available closely-relatedclosely related organisms, and the high rate of homology among M. fructicola genes points towards a recent whole-genome duplication event as the cause of this large genome. Based on the assembled genome, sequences were annotated with a gene description and gene ontology (GO term) and clustered in functional groups. Analysis of CAZymes family genes revealed 1,145 putative genes, and transcriptomic analysis of CAZyme expression levels in M. fructicola during its interaction with either grapefruit peel tissue or Penicillium digitatum revealed a high level of CAZyme gene expression when the yeast was placed in wounded fruit tissue.